Analyzing Parental Age to Determine Types of Cleft in Hayandra Peduli Foundation Patient, Indonesia - Karina Karina; Fransisca Fransisca; Kevin Leonard Suryadinata (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2020)
Cleft lip and palate are complex and known to have multifactorial risk factors with a prevalence of 0.2% in Indonesia. Also, there is no specific data about parental age-related to types of a cleft in Indonesia. This study aims to analyze parental age-related to types of cleft in patients treated by Hayandra Peduli Foundation, Indonesia. The data was collected from 2014 to 2018 from social service held by Hayandra Peduli Foundation. The data collected primarily, and 604 subjects were obtained. The results showed that 81.5% of patients were 0-5 of age, with patients' distribution were 356 male patients and 248 female patients. There was no significant correlation between maternal age and each type of cleft. Furthermore, there was no correlation between paternal age and types of cleft based on maternal group age. For young and ideal maternal group age, their p-value showed no significant correlation (p-value 0.393 for young maternal age and 0.941 for ideal maternal age). Surprisingly, the old maternal group age shows significant results, with a p-value of 0.045. In conclusion, we found that cleft palate will occur in infants born from an aging mother (>35 years old).